Microscale Thermophoresis Reveals Oxidized Glutathione as High-Affinity Ligand of Mal d 1 - Soraya Chebib; Wilfried Schwab (Foods, 2021)
Pathogenesis-related (PR)-10 proteins, due to their particular secondary structure, can bind various ligands which could be important for their biological function. Accordingly, the PR-10 protein Mal d 1, the major apple allergen, probably also binds molecules in the hydrophobic cavity of its secondary structure, but it has not yet been investigated in this respect. In this study, various natural products found in apples such as flavonoids, glutathione (GSH), and glutathione disulfide (GSSG) were investigated as possible ligands of Mal d 1 using microscale thermophoresis. Dissociation constants of 16.39 µM, 29.51 µM, 35.79 µM, and 0.157 µM were determined for catechin, quercetin-3-O-rhamnoside, GSH, and GSSG, respectively. Molecular docking was performed to better understand the underlying binding mechanism and revealed hydrophobic interactions that stabilize the ligands within the pocket while hydrophilic interactions determine the binding of both GSH derivatives. The binding of these ligands could be important for the allergenicity of the PR-10 protein and provide further insights into its physiological role.